Pacific peoples’ perspectives on spiritual health : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Public Health in Public Health at Massey University, Wellington, New Zealand - Hitti, Penina Ruhiyyih (Massey University, 2024)
This research investigates Pacific peoples’ perspectives on spiritual health and how this perspective contributes to the discourse on social determinants of health for inclusion in public health programmes and approaches. Pacific views on the value of holistic health and cultural principles are fundamental in addressing health inequities for Pacific people. Within the context of public health, the aim of the research examines the relationship between spirituality and wellbeing, acknowledging the interconnectedness of spiritual health with physical, mental, and social health. The research methods of inquiry includes an extensive literature review to identify a definition of spiritual health, considering historical influences and the potential challenges that present themselves when efforts are made to fit indigenous knowledge into existing health frameworks. The study also uses a qualitative methodology and adopts Pacific Talanoa for its focus group discussion among Pacific peoples representing different religious backgrounds. The findings highlight four main themes as a result of the focus group (1) interconnectedness of spiritual health with other areas of health; (2) importance of spiritual health practices; (3) influence of religious and cultural factors; and (4) interdependence of spiritual health on individual, familial, communal, and environmental health. In conclusion, this study found that spiritual health has a significant role in promoting holistic wellbeing and health for Pacific peoples. By including and incorporating cultural and religious elements into health interventions, public health professionals and researchers may be able to develop more effective strategies to address health disparities and promote equitable health outcomes for Pacific people.
Keywords: 451614 Pacific Peoples public health and wellbeing